Scientific approaches to the definition of the boundaries of state intervention in the redistribution of income - Vlasiuk, V. Ye. (Science and Transport Progress, 2008)
The paper is devoted to theoretical and methodic problems of research of factors of influence of the state regulation of the processes of incomes distribution. The efficiency of state regulation of redistribution of incomes is analyzed.